2017
DOI: 10.1016/j.apmr.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Work Limitations 4 Years After Mild Traumatic Brain Injury: A Cohort Study

Abstract: Although changes in employment status and difficulties at work are likely over time, the results indicate increased unemployment rates, work limitations, and productivity loss in the longer term after a mild TBI. Identification of cognitive difficulties 1 month after TBI in working aged adults and subsequent interventions to address these difficulties are required to facilitate work productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 24 publications
3
51
0
Order By: Relevance
“…No significant between-group differences were found in household tasks, learning, community life, emotional functions, concentrating, dealing with strangers, or maintaining friendships, where impairment was rated as around moderate in all 3 patient groups. This study is in line with previous studies showing a high proportion of residual complaints in patients with TBI, even in those with miTBI and even after years of injury (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Based on our results, the functioning assessments by patients, significant others and treating neurologists were largely in line and thus probably also reliable.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No significant between-group differences were found in household tasks, learning, community life, emotional functions, concentrating, dealing with strangers, or maintaining friendships, where impairment was rated as around moderate in all 3 patient groups. This study is in line with previous studies showing a high proportion of residual complaints in patients with TBI, even in those with miTBI and even after years of injury (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Based on our results, the functioning assessments by patients, significant others and treating neurologists were largely in line and thus probably also reliable.…”
Section: Discussionsupporting
confidence: 92%
“…When patients with different injuries are evaluated, TBIs cause the most severe health issues (4) and long-lasting consequences for both physical and mental health (5,6) irrespective of the severity of injury (7). Even mild TBI (miTBI) may cause a diversity of problems in cognitive and emotional functions, energy and drive, and in carrying out daily routines and work (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…These findings compliment previous research which has highlighted the impact of mild-TBI on work productivity four years after mild-TBI. [ 6 , 25 ] Indeed, a changing sense of self, needing to manage limitations caused by the TBI symptoms and needing support to cope with the unpredictability of the future have been important factors affecting employment following mild-TBI. The current findings highlight that the impact of mild-TBI extends beyond paid employment and also affects wider community participation.…”
Section: Discussionmentioning
confidence: 99%
“…These include cognitive (e.g., difficulty concentrating and taking longer to think), somatic (e.g., headaches, fatigue or dizziness) and emotional symptoms (e.g., feeling irritable, frustrated or restless). [ 5 ] Cognitive symptoms have been linked to reduced productivity at work,[ 6 , 7 ] higher health service use, and engagement in antisocial behaviour. [ 8 ] Whilst many recover naturally from mild-TBI within weeks or months of the injury,[ 9 , 10 ] evidence has now revealed that symptoms can persist for between 24% and 48% of those experiencing a mild-TBI one year post-injury.…”
Section: Introductionmentioning
confidence: 99%
“…15 Traditionally, mTBI has been thought to require minimal clinical management beyond watchful waiting. 16 In response to mounting evidence that mTBI can be associated with chronic symptoms and disability, [17][18][19][20] standards for mTBI care have evolved to promote earlier and more proactive intervention. [21][22][23][24] Numerous expert agreement statements and clinical practice guidelines have been published within the last 5 years.…”
mentioning
confidence: 99%